New developments in statistical modeling, inference and application : selected papers from the 2014 ICSA/KISS Joint Applied Statistics Symposium in Portland, OR /: selected papers from the 2014 ICSA/KISS Joint Applied Statistics Symposium in Portland, OR. (2016) - Unknown
No abstract available